Bank capital buffers in a dynamic model - Jochen Mankart; Alexander Michaelides; Spyros Pagratis (Deutsche Bundesbank, 2018)
We estimate a dynamic structural banking model to examine the interaction between risk-weighted capital adequacy and unweighted leverage requirements, their differential impact on bank lending, and equity buffer accumulation in excess of regulatory minima. Tighter risk-weighted capital requirements reduce loan supply and lead to an endogenous fall in bank profitability, reducing bank incentives to accumulate equity buffers and, therefore, increasing the incidence of bank failure. Tighter leverage requirements, on the other hand, increase lending, preserve bank charter value and incentives to accumulate equity buffers, therefore leading to lower bank failure rates.
Keywords: E44; G21; G38; 330; Banking; Equity Buffers; Regulatory Interactions